The procedure and purpose of protective measures for the child, girl and adolescent under the age of 14 that creates a conflict with criminal law - Fernández Arias, Luis Miguel (2016)
Through this work, we want to call for reflection to all legal operators involved in the issue of children and adolescents under 14 years of age who come into conflict with the criminal law by having committed unlawful acts. We notice the lack of clear and precise rules that allow us to determine what is the most suitable and adequate protection measure for this child population. Similarly, , we intend to promote a healthy debate on what is the purpose of the tutelary processes that are established for this purpose, since at the beginning we consider that these tutelary are different from the processes that are established for reasons of abandonment.